Experimental and theoretical review on covalent coupling and elemental doping of carbon nanomaterials for environmental photocatalysis. Issue 2 (4th March 2023) - Arooj, Mahreen; Parambath, Javad B. M.; Ali, Nisar; Khan, Adnan; Malik, Sumeet; Bilal, Muhammad; Mohamed, Ahmed A.
Abstract: Carbon nanomaterials (CNMs) are outstanding photocatalysts for tackling environmental issues, however, their pristine forms possess poor dispersibility and limited stability under photocatalytic conditions. The impediments of using CNMs in environmental applications can be challenged by covalent coupling and elemental doping. With these caveats in mind, we address our perspectives from chemistry and engineering concepts to benefit from CNMs in water decontamination. Compiled data from density functional theory (DFT) and molecular dynamics simulation support that the changes in the physicochemical properties can enhance the durability and functionality of CNMs in environmental remediation. This review critically analyzes experimental and theoretical approaches related to the functionalization of CNMs by covalent coupling and elemental doping for environmental photocatalysis. Abstract : UF0001